Distribution and accumulation of artificial radionuclides in marine products around Korean Peninsula. (September 2019) - Kim, Suk Hyun; Lee, Hyunmi; Lee, Sang Han; Kim, Intae
Abstract: We investigated the distributions of the artificial radionuclides 137 Cs, 239+240 Pu, and 90 Sr in the various marine products around Korean Peninsula collected in 2015–2017. The activities of 137 Cs, 239+240 Pu, and 90 Sr were in the ranges of 12.2–258.4 mBq kg − 1, 0.014–1.879 mBq kg − 1, and 11.3–18.3 mBq kg − 1, respectively. The higher 239+240 Pu (a factor of 10–50) relative to fishes were observed in mollusks. 137 Cs in fishes were significantly enriched with growths. The calculated concentration factors (CFs) of 137 Cs, 239+240 Pu, and 90 Sr in marine products were 7–143, 3–407, and 15–25, respectively. Overall, no noticeable artificial radioactivity was detected in marine organisms when comparing these results with previous data reported before the Fukushima nuclear accident and recommended CF values. The annual effective doses of 137 Cs, 239+240 Pu, and 90 Sr by seafood consumption in South Korea were estimated to be 1.1 × 10 − 4, 1.6 × 10 − 5 and, 2.9 × 10 − 5 mSv yr − 1, respectively, which is insignificant relative to that of natural radionuclides. Highlights: Artificial radionuclides (ARs) were determined in marine products around South Korea. No significant spatiotemporal variation of 137 Cs, 239, 240 Pu, 90 Sr in marine biota 137 Cs and 239, 240 Pu in marine biota could vary according to main habitats and growth. 137 Cs activity in fishes except salmon logarithmically correlated with body weight. Annual dose of ARs were insignificant relative to those of natural radionuclides.